De vivências e conversas - o protagonismo feminino na migração venezuelana - Freitas, Maria Inah de Almeida (2021)
During past centuries, women were hidden from academic research and production. Facing the migratory context, migrant women were also victims of this movement of exclusion and historical invisibility. Only in the 80s, following the rise of feminist movements that founded analyzes and reflections from the gender perspective, was that it became possible to develop research and academic work, bringing to light the importantpresence of women in different migratory circulations. The feminization of international migration is the result of this disruption with patriarchal and androcentric science and emerges as a process of breaking paradigms, which promotes the construction of an epistemology using, as a foundation, the gender perspective. The present work, of qualitative nature and ethnographic approach, was developed using the feminization of migration as a starting point, in order to demonstrate the protagonism of a group of Venezuelan women facing the challenges imposed by the migratory reality in the city of Manaus. The analysis of theory and data collected was based according to the perspective of gender, and its collection was carried out through interviews, field diary and participant observation. In this context, we selected the main difficulties that most appeared in the narratives of the participants, which made visible the protagonism of these women, being them: difficulty in including the children from the participants in the public school system, insertion in labor market, poor remuneration, unhealthy conditions, for those who work autonomously and not, and obstacles encountered in relation to migratory regularization. Soon, we concluded that, despite the obstacles described being part of the collaborators' daily life, the protagonism in this issue is real and potent. They have an active role in the city of Manaus, moving the economy, creating effective strategies for both job insertion and resolving demands related to migratory regularization, besides presenting a great potential for creating and maintaining migratory networks, also achieving goals through these women's networks.